(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Extra pulmonary tuberculosis accounts for 20% of all tuberculosis cases, among them 35% are tuberculous lymphadenitis. Persistent and/or paradoxically enlarged lymph node, newly developed lymph node as well as suppuration of the lymph node give rise to controversies about duration of therapy, mode of treatment and further evaluation. Various outcomes not only affect the patients psycho-socially and economically but also burdened the country’s Tuberculosis Control Program me. So it is wise to search the possible links to prevent these situations. Vitamin D has a significant role in stimulating macrophage and the subsequent limitation of Mycobacterium tuberculosis growth as well as acceleration of resolution of inflammatory responses secondary to it which is mainly responsible for these various outcomes. The present study was attempted to determine the status of serum vitamin D concentration in patient with tuberculous lymphadenitis and to compare it with apparently healthy controls. Materials and methods: This case-control study was conducted in the Department of Internal Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU) between May 2016 and March 2017.Thirtyone (31) newly diagnosed patients of tuberculous lymphadenitis were selected as cases and equal numbers of age-sex matched apparently healthy individuals were taken as controls for the study. Different diagnostic modalities (FNAC, Histopathology and PCR) were employed to diagnose the cases. Blood samples were collected and estimated for serum vitamin D [25(OH) D] by Chemiluminescent Immunoassay (CLIA) method. Serum vitamin D <20 ng/ml was considered as vitamin D deficiency. The exposure and outcome variables were level of serum vitamin D and tubercular lymphadenitis. The results were analyzed on SPSS version 20. Results: Mean (±SD) serum vitamin D levels were 13.08±6.32 ng/ml in cases and 21.08±4.5 ng/ml in controls (p<0.001). Over 80% of the cases had low serum vitamin D as compared to 35.5% of the controls. More than 70% of the cases exhibited severe deficiency (£15ng/mL), 9.7% deficiency (<20 ng/ml) and16.2% insufficiency (20 – 30 ng/mL) of serum vitamin D, whereas in the control group 6.5% were severely deficient, 29.1% deficient and 61.3% were insufficient. The odds ratio corresponding to serum vitamin D level <20 ng/ml in case group were 7.5 (95% CI = 2.3 – 24.1, p<0.001). Conclusion: Tubercular lymphadenitis patients had significantly lower serum vitamin D level in comparison to control. This association of low serum vitamin D level in tuberculous lymphadenitis patients may be bidirectional, either low serum vitamin D level increases the risk of tuberculous lymphadenitis or tuberculous lymphadenitis may be a risk factor for low serum vitamin D concentration. JCMCTA 2024 ; 35 (2) : 35-41